2015
DOI: 10.15436/2377-0619.15.016
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Fatty Acids Improve Lipid Metabolism and Inflammatory Markers in Patients with Heart Failure Undergoing Exercise Training

Abstract: We hypothesize whether omega-3 (n-3) polyunsaturated fatty acids (PUFA) supplementation may improve the lipid metabolism and inflammatory biomarkers in heart failure (HF) patients undergoing exercise training. Sixteen male patients, who were participating in a physical cardiac rehabilitation program, ingested 4.8 g of fish oil daily (2.51 g of eicosapentaenoic and docosahexaenoic acids) for 60 days. Blood samples were collected at baseline and after 60 days of n-3 PUFA supplementation for analysis. The paired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Although these results have been demonstrated by studies conducted in several different populations [ 40 42 ], those examining the effects of omega-3 PUFAs supplementation on IL-10 in patients with HF presented controversial results. For instance, no changes for IL-10 were observed in a study including 16 male patients with HF that received omega-3 PUFAs supplementation during 60 days [ 43 ]. In addition, another study including 190 patients with paroxysmal or persistent atrial fibrillation showed no significant effects of omega-3 PUFAs supplementation on IL-10 concentration after a 6-month period [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although these results have been demonstrated by studies conducted in several different populations [ 40 42 ], those examining the effects of omega-3 PUFAs supplementation on IL-10 in patients with HF presented controversial results. For instance, no changes for IL-10 were observed in a study including 16 male patients with HF that received omega-3 PUFAs supplementation during 60 days [ 43 ]. In addition, another study including 190 patients with paroxysmal or persistent atrial fibrillation showed no significant effects of omega-3 PUFAs supplementation on IL-10 concentration after a 6-month period [ 44 ].…”
Section: Discussionmentioning
confidence: 99%